Robôcactus: uma proposta para a prática de lógica de programação por meio da Robótica Educacional e da plataforma Arduino na Educação Profissional e Tecnológica. - Ramos, Bruno Amorim (2021)
The present research aims to present the results of the application of the educational product Robocactus as a tool for praxis in Professional and Technological Education (EFA), illustrating the reality of the educational product before the pandemic of COVID-19, in a face-to-face setting through a workshop, and also during the pandemic with the use of virtual resources in Distance Education (DL). For this, the use of the theoretical and methodological apparatus of educational robotics and the Arduino platform was deemed necessary. This work used the methodology of participant-action research and the active methodologies of Inverted Classroom (SAI) and Project Based Learning (ABP). Given the difficulties and lack of motivation of students in the programming logic component, a methodology was developed that aims to mitigate the dichotomy between theory and practice, allowing a glimpse to contribute to the formation of critical thinking and technical knowledge of the student, which are important factors for human and professional development in the 21st century. The data survey relied on the application of semi-structured questionnaires. Finally, content analysis revealed the positive experience of using robotics as a technological motivator in the school environment, as well as the development of broad concepts about robotics, computer programming, and Arduino.